2020
DOI: 10.3892/ol.2020.11540
|View full text |Cite
|
Sign up to set email alerts
|

Pathological roles of c‑Met in bladder cancer: Association with cyclooxygenase‑2, heme oxygenase‑1, vascular endothelial growth factor‑A and programmed death ligand�1

Abstract: c-Met is a receptor tyrosine kinase that binds a specific ligand, namely hepatocyte growth factor (HGF). The HGF/c-Met system is important for malignant aggressiveness in various types of cancer, including bladder cancer (BC). However, although phosphorylation is the essential step required for biological activation of c-Met, pathological roles of phosphorylated c-Met at the clinical and molecular levels in patients with BC are not fully understood. In the present study, the expression levels of c-Met and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In F. hepatica infection it induces production of IL-10 which is necessary for parasite establishment in the host 51 . Of note, hepatocyte growth factor receptor induces Ras-dependent upregulation of both HO-1 and PD-L1 in cancer 56 , 57 . In addition, myeloid cells expressing both HO-1 and PD-L1 in breast tumors suppress T cell activity 58 .…”
Section: Discussionmentioning
confidence: 99%
“…In F. hepatica infection it induces production of IL-10 which is necessary for parasite establishment in the host 51 . Of note, hepatocyte growth factor receptor induces Ras-dependent upregulation of both HO-1 and PD-L1 in cancer 56 , 57 . In addition, myeloid cells expressing both HO-1 and PD-L1 in breast tumors suppress T cell activity 58 .…”
Section: Discussionmentioning
confidence: 99%
“…47 Their subsequent studies suggested that two c-Met tyrosine residues, pY1234/pY1235 and pY1349, were related to muscular infiltration and metastasis, while c-Met itself was only significantly associated with muscular infiltration. 48 In contrast, Iyer et al found a nonsignificant association between HGF/c-Met immunoreactivity and tumour stage, grade and overall patient survival. 34 In parallel, Yeh et al found that c-Met expression did not correlate with tumour grade or lymph node involvement.…”
Section: Dovepressmentioning
confidence: 94%
“…Furthermore, they demonstrated possible links between pY1349 c-Met and cancer-related substances such as cyclooxygenase-2 (COX-2), haem oxygenase-1 (HO-1) and programmed death ligand 1 (PD-L1). 48 Intriguingly, the upstream mediator of pY1349 c-Met might be SRY-box 18 (SOX18), which was proven to promote carcinogenesis and progression of BCa. In such a study, Huaqi et al observed an augmented level of phosphorylated pY1349 c-Met in SOX18-elevated BCa cells, and after applying cabozantinib, a c-Met suppressor, the migration capability of SOX18-elevated BCa cells was dramatically compromised.…”
Section: Dovepressmentioning
confidence: 99%
“…In addition, the correlation between c-Met and programmed death ligand 1 (PD-L1) in tumor tissues was investigated. Y. Mukae et al (38) demonstrated that the high expression of c-Met was correlated with muscle invasion and metastasis of BCa, and c-Met exerted a vital function in invasion of tumor cell by regulating PD-L1. This study shows that c-Met is indeed involved in the invasion and metastasis of BCa, which again theoretically confirms that c-Met may affect the prognosis and survival of BCa patients.…”
Section: Bladder Cancermentioning
confidence: 99%